Ultra-rapid activation and deactivation of store-operated Ca(2+) entry in skeletal muscle. - Edwards, Joshua N.; Murphy, Robyn M; Cully, Tanya R.; von Wegner, Frederic; Friedrich, Oliver; Launikonis, Bradley S. (Cell calcium, 2010)
Skeletal muscle is highly specialized for the rapid delivery of Ca(2+) to the contractile apparatus during excitation-contraction coupling (EC coupling). Previous studies have shown the presence of a relatively fast-activated store-operated Ca(2+) entry (SOCE) mechanism (<1s) to be present in skeletal muscle, unlike the situation occurring in non-excitable cells. We simultaneously imaged [Ca(2+)] in the t-system and cytoplasm in mechanically skinned fibers during SR Ca(2+) release and observed both cell-wide Ca(2+) release and Ca(2+) waves. SOCE activation followed cell-wide Ca(2+) release from high sarcoplasmic reticulum (SR) [Ca(2+)] ([Ca(2+)](SR)) by seconds, consistent with depletion of [Ca(2+)](SR) to an absolute threshold for SOCE and an unformed SOCE complex at high [Ca(2+)](SR). Ca(2+) waves occurred at low [Ca(2+)](SR), close to the threshold for SOCE, minimizing the time between Ca(2+) release and Ca(2+) influx. Local activation of SOCE during Ca(2+) waves occurred in approximately 27ms following local initiation of SR depletion indicating a steep relationship between [Ca(2+)](SR) and SOCE activation. Most of this delay was due to slow release of Ca(2+) from SR, leaving only milliseconds at most for the activation of Ca(2+) entry following store depletion. SOCE was also observed to deactivate effectively instantly during store refilling at low [Ca(2+)](SR). These rapid kinetics of SOCE persisted as subsequent Ca(2+) waves propagated along the fiber. Thus we show for the first time millisecond activation and deactivation of SOCE during low amplitude [Ca(2+)](SR) oscillations at low [Ca(2+)](SR). To account for the observed Ca(2+) movements we propose the SOCE complex forms during the progressive depletion of [Ca(2+)](SR) prior to reaching the activation threshold of SOCE and this complex remains stable at low [Ca(2+)](SR).
Keywords: Skeletal muscle; Excitation–contraction coupling; Ryanodine receptor; Store-operated Ca2+ entry; t-system; Sarcoplasmic reticulum